Effect of welding heat input to metal droplet transfer characterized by structure-borne acoustic emission signals detected in GMAW. (June 2015) - Yi, Luo; Yan, Zhi; Xiaojian, Xie; Yang, Zhu; Rui, Wan
Highlights: It is possible to study the metal droplet transfer by AE signals detected in welding. The MDT frequency are increased along with the raise of welding heat input. The power spectrum distribution of AE signals for MDT was different. The waves of AE signals was different as the metal droplet transfer were various. The energy gradient of metal droplet transfer was increased with the heat input. Abstract: The structure-borne acoustic emission (AE) signals during gas metal arc welding (GMAW) on 2024 aluminum alloy were detected in real-time and analyzed to find the characteristics of metal droplet transfer (MDT) in welding process. The analysis of time domain and frequency domain was introduced. The energy gradient was used to describe the rate of energy variation during the metal droplet transfer. The results showed that the MDT event of AE signals reflects a mass of transient information about metal droplet transfer in GMAW process. The MDT frequency and the average grain size were increased along with the raise of welding heat input. The increasing welding heat input raised the MDT frequency and the energy input by the metal droplet transferred into the molten pool. According to the energy gradient, the process of short-circuiting transfer of metal droplet was comprised of three parts. The energy gradient and energy transfer coming from the metal droplet transfer were increased along with the welding heat input raised in GMAW process. Therefore, it is possible to study the metal droplet transfer of GMAW by the analysis to the AE signals detected in welding.